Discourses of practice: an examination of KEF and its effects on the AL/HRD community. (2nd September 2021) - Ross, Catharine; Nichol, Lynn; Elliott, Carole; Sambrook, Sally; Stewart, Jim
ABSTRACT: The contribution of scholarship to practice is an on-going concern of the AL/HRD community. This paper explores how one influential discourse may shape AL/HRD's understanding of that contribution. In 2020 the UK Government implemented the Knowledge Exchange Framework (KEF) to gather data on English Universities' knowledge exchange activities. Using Gee's tools of enquiry and building tasks we undertook discourse analysis of two key KEF texts to explore its likely impact on the AL/HRD community's understanding. We compare the discourses used in those texts with three AL/HRD orders of discourse identified in existing literature to explore which if any are reinforced by the KEF discourses, and the potential material consequences this may have for AL/HRD understandings and practice. We find evidence of performance/performance discourses but no evidence of learning/emancipatory and critical discourses in the first text, but some limited elements of learning/emancipatory and critical discourses in the second. In contrast to models of inter-organisational learning, analysis of other texts referred to in this second source suggests that this change did not arise from the documented formal processes but micro-level informal interactions. We suggest this gives individual AL/HRD community members the space to develop alternative, non-performance discourses and practices of knowledge exchange.